Chronic Non- Peurperal Uterine Inversion: Recommendations for Diagnosis and Management (Global Journal of Medical Research, 2014)
Inversion of the uterus is a rare clinical condition. Further, chronic non-puerperal uterine inversion is a still rare clinical entity with very few clinicians encountering it. Intra-uterine tumours; especially large fundal submucosal leiomyomas are the usual precipitating factors. Due to its extremely rare occurrence it may pose a diagnostic as well as surgical challenge for the gynaecologist. Correct diagnosis based on clinical findings & diagnostic modalities like Ultrasonography (USG) and Magnetic Resonance Imaging (MRI) careful preoperative planning & appropriate surgical procedure are imperative for a successful outcome. We propose certain recommendations for diagnosis and management of chronic non puerperal uterine inversion associated with a large prolapsed fundal submucosal fibroid accurate diagnosis commencing with strong clinical suspicion & confirmation with advanced diagnostic modalities is the cornerstone of management. HYSTERECTOMY is difficult with the grossly distorted anatomy. A well planned and carefully executed surgery ensures a good outcome with minimum morbidity.
Keywords: chronic non-puerperal uterine inversion; ultrasonography; magnetic resonance imaging; hysterectomy